2020
DOI: 10.3390/biom10040514
|View full text |Cite
|
Sign up to set email alerts
|

Glycofullerenes Inhibit Particulate Matter Induced Inflammation and Loss of Barrier Proteins in HaCaT Human Keratinocytes

Abstract: Exposure to particulate matter (PM) has been linked to pulmonary and cardiovascular dysfunctions, as well as skin diseases, etc. PM impairs the skin barrier functions and is also involved in the initiation or exacerbation of skin inflammation, which is linked to the activation of reactive oxygen species (ROS) pathways. Fullerene is a single C60 molecule which has been reported to act as a good radical scavenger. However, its poor water solubility limits its biological applications. The glyco-modification of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…Eudragit nanoparticles encapsulating eupafolin significantly attenuated PM-induced ERK, p38, and JNK phosphorylation and downregulated the expression of cyclooxygenase, prostaglandins (Figure 3; Lin et al, 2016). Similar effects were seen with fullerene particle which decreased oxygen scavenging pathways (C. W. Lee, Su, et al, 2020).…”
Section: Effect On Map-kinase Pathwaysupporting
confidence: 67%
See 1 more Smart Citation
“…Eudragit nanoparticles encapsulating eupafolin significantly attenuated PM-induced ERK, p38, and JNK phosphorylation and downregulated the expression of cyclooxygenase, prostaglandins (Figure 3; Lin et al, 2016). Similar effects were seen with fullerene particle which decreased oxygen scavenging pathways (C. W. Lee, Su, et al, 2020).…”
Section: Effect On Map-kinase Pathwaysupporting
confidence: 67%
“…Modified C60 called glycofullerene reduced the PM-induced apoptosis in keratinocytes and also prevented oxidative stress. Glycofullerene also maintained barrier properties of keratinocytes indicating their role in developing antipollution platforms (C. W. Lee, Su, et al, 2020).…”
Section: Protection Against Pollutantsmentioning
confidence: 98%
“…In this study, we used anti-Krt15 antibodies to measure the purity of keratinocytes. Furthermore, it was previously also reported that loricrin was detected in human keratinocytes by Western blot [ 25 ]. Consistent with previous reports, we also found that the gene is highly expressed in primary mouse keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [100] investigated fullerene, according to its good radical scavenger properties, in the treatment of particulate matter (PM) that induces skin diseases and pulmonary and cardiovascular disfunctions. Indeed, PM is involved in skin inflammation and in the activation of ROS.…”
Section: Indirect Actionmentioning
confidence: 99%